2021
DOI: 10.3389/fmars.2021.701332
|View full text |Cite
|
Sign up to set email alerts
|

Use of an INLA Latent Gaussian Modeling Approach to Assess Bird Population Changes Due to the Development of Offshore Wind Farms

Abstract: The utilization of marine renewable energies such as offshore wind farming leads to globally expanding human activities in marine habitats. While knowledge on the responses to offshore wind farms and associated shipping traffic is accumulating now at a fast pace, it becomes important to assess the population impacts on species affected by those activities. In the North Sea, the protected diver species Red-throated Diver (Gavia stellata) and Black-throated Diver (Gavia arctica) widely avoid offshore wind farms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
2
10
0
3
Order By: Relevance
“…6) and statistical analyses of individual repeatability (Table A1) show an individual consistent site use in consecutive years, considered over a broad scale. Combined with the findings of Mendel et al (2019) and Vilela et al (2021), these data suggest that red-throated divers are somewhat flexible to change sites at small scales, but may have limited flexibility to change sites at large scales in response to large-scale habitat loss.…”
Section: Do Individuals Faithfully Utilise Areas During Their Key Lif...supporting
confidence: 51%
See 4 more Smart Citations
“…6) and statistical analyses of individual repeatability (Table A1) show an individual consistent site use in consecutive years, considered over a broad scale. Combined with the findings of Mendel et al (2019) and Vilela et al (2021), these data suggest that red-throated divers are somewhat flexible to change sites at small scales, but may have limited flexibility to change sites at large scales in response to large-scale habitat loss.…”
Section: Do Individuals Faithfully Utilise Areas During Their Key Lif...supporting
confidence: 51%
“…If habitat selection is driven by a macro-selection, it could be that habitat change has an effect on a smaller spatial scale and displacement is a process happening at smaller scales. However, in this context, results from studies on red-throated diver distributions and displacement effects in the eastern German Bight showed that red-throated divers remained in the general area, but shifted their distribution and congregated outside disturbed areas (Mendel et al 2019;Vilela et al 2021). Mendel et al (2019) analysed long-term datasets of aerial and ship based surveys, whereas Vilela et al (2021) analysed long-term datasets of aerial surveys.…”
Section: Do Individuals Faithfully Utilise Areas During Their Key Lif...mentioning
confidence: 99%
See 3 more Smart Citations